Ductography and Microdochectomy: the Diagnostic Procedure of Choice Alongside the Conventional Tools for Nipple discharge - Awwal, Rayhana; Seraji, Ahmad; Ahsanullah, Md Redwan; Rupa, Sharmin Akhtar; Akhter, Shabnam; Joarder, Ruhul Hassan (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: Nipple discharge is the presenting complaint in 3-10% of all women with breast-related complaints. It causes considerable anxiety in the modern cancer-conscious woman. Breast surgeons frequently use various tools for diagnosing the underlying cause of nipple discharge. A definitive diagnostic approach is crucial for an accurate diagnosis of the aetiology and exclusion of any malignant breast lesion. The objective of this study was to evaluate diagnostic performances of ductography and microdochectomy and compare these with other conventional diagnostic tools. Methods: This retrospective study included 153 female patients presenting with significant nipple discharge to “Breast Care Center” from December 2011 to December 2018. Informed consent was taken from all participants. History, clinical examination, relevant imaging, cytology and histology findings of all the patients were recorded in electronic database. Results: Mean and median age of the cohort were 38.4 years and 35 years respectively. 18 of the 153 patients, had a positive family history for breast cancer which was statistically significant. 3.9% (6/153) patients were eventually diagnosed (cytopathology-1, FNAC-1, ductography-1 & microdochectomy-3) with in situ or invasive malignancies while being evaluated for nipple discharge. Breast ultrasound has sensitivity and specificity of 28.6% (5.1-69.7) & 99.3% (95.7-99.9) respectively at 95% CI in detecting risk lesions. Sensitivity of ductography in detecting risk lesions was 100% (95% CI: 5.4-100) with specificity value of 95.2% (95% CI: 85.8-98.8). Again, microdochectomy has been used as final diagnostic as well as therapeutic tools in the study. Conclusion: Ductography is a noninvasive imaging modality whereas microdochectomy, although invasive, helps reach a definitive tissue diagnosis. Ductography and microdochectomy together can serve as indispensable diagnostic tools alongside the conventional radiological and histological tools. J Bangladesh Coll Phys Surg 2022; 40: 263-269